2018
DOI: 10.1017/s1092852918001207
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in major depressive disorder

Abstract: Cognitive dysfunction is a symptomatic domain identified across many mental disorders. Cognitive deficits in individuals with major depressive disorder (MDD) contribute significantly to occupational and functional disability. Notably, cognitive subdomains such as learning and memory, executive functioning, processing speed, and attention and concentration are significantly impaired during, and between, episodes in individuals with MDD. Most antidepressants have not been developed and/or evaluated for their abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(94 citation statements)
references
References 78 publications
(144 reference statements)
5
86
0
3
Order By: Relevance
“…Although MDD is thought of as a primarily affective disorder, it is increasingly acknowledged that cognitive dysfunction is common among MDD patients and contributes profoundly to the disease burden 43,44 . While affective dysfunction and cognitive disturbance co-occur during depressive episodes, these symptoms can also be experienced independently of one another.…”
Section: Discussionmentioning
confidence: 99%
“…Although MDD is thought of as a primarily affective disorder, it is increasingly acknowledged that cognitive dysfunction is common among MDD patients and contributes profoundly to the disease burden 43,44 . While affective dysfunction and cognitive disturbance co-occur during depressive episodes, these symptoms can also be experienced independently of one another.…”
Section: Discussionmentioning
confidence: 99%
“…67 In addition to their involvement with mood symptomatology, cytokines are involved in cognitive functions such as attention, executive function, learning, and memory, which may contribute to the cognitive impairment observed in MDD. 68,69 The proposed mechanism by which cytokines affect the nervous system is complex; in summary, they can evoke an excitotoxic effect by way of interactions between the monoamine, glutamate, and BDNF systems. 70 Given their involvement in neurotransmitter systems and associated symptomatologic presentation, reduction of inflammatory cytokines presents a novel therapeutic pathway.…”
Section: Immune-inflammationmentioning
confidence: 99%
“… 12 Therefore, increasing studies have focused on the treatment of cognitive impairment, and have shown certain advantages. 13 However, there is still no better way to improve cognitive function.…”
Section: Discussionmentioning
confidence: 99%